PENGEMBANGAN MODEL PEMBELAJARAN MULTI METODE DALAM PENINGKATAN HASIL BELAJAR SISWA - ROSFIANI, OKTA (PPs UNJ, 2012)
Education can be interpreted as a process with certain methods therefore man obtains knowledge, understanding, and way of behaviour matching with requirement. In election and usage of method must consider its(the evektifity aspect and its(the relevensi with the matter related. Skill uses various representing one of skill teachs which must be mastered by teacher. In process of study, not rarely rutinity which is performed by teacher like discourse, question and answer, then discuses with group makes bored and saturated student. In condition like this teacher must clever uses method teachs that is by changed style teachs, by using model multi method (Study Model of Interaktif Teacher-Centered, Study Model of Interaktif which Student-centered). Therefore student do not feel bored and can create more pleasant study situation. Through Multi this Metode, teacher creates the situation which pushs so that student feeling requiring each other. Relation requiring each other this can generate existence of positive interdependence which claims existence of possible interaction the neighbouring student giving each other motivation to gain result of optimal achievement.Keywords: Education, Study, Multi Method